Korelasi Indeks Massa Tubuh dengan Kadar Kolesterol Total pada Mahasiswa Pre Klinik Fakultas Kedokteran Universitas Andalas - Zikra Muhammad; Julizar Julizar; Avit Suchitra (Jurnal Ilmu Kesehatan Indonesia, 2022)
The increase in body mass index is a condition were excessive increase in fat accumulation in adipose tissue so it can be detrimental to health. Increase in lipid metabolism can trigger the increase in cholesterol level inside the body. This study  aimed to know the correlation between body mass index and total cholesterol level on Medical Faculty of Andalas University pre clinic student.